The Criminal Penal Policy in Iraqi law of Drugs and Mental Detectives No.50 for 2017 - Usama Al-naimi (الرافدین للحقوق, 2019)
Abstract This research is an attempt to highlight the criminal penal policy adopted by the Iraqi legislator in the Law on Narcotic Drugs and Psychotropic Substances No. 50 of 2017, especially in light of the spread of the phenomenon of trafficking and illegal handling of narcotic drug or psychotropic substances and the widening circle of abuse and addiction , The Iraqi street at various levels because of its negative effects seriously threaten the society at large at all levels of social, economic and health, and to indicate the extent to keep pace with this policy of contemporary penal policy, as well as the extent of its adequacy in combating the phenomenon of non-interference Intimidation of narcotics or psychotropic substances in all its forms or at least to reduce them .